ANALYSIS OF FACTORS INFLUENCING THE EXCHANGE RATE OF FARMERS IN THE MAIN FOOD CROP SUB-SECTORS IN JAMBI PROVINCE: English - Siadari, Ulidesi; Fauzia, Gina; Ningsih, Rozaina; Rahayu, Vika Indah (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
This study aimed to analyze the factors that influence the exchange rate of farmers in the primary food crop subsector in Jambi Province. The scope of this study is the influence of rice and corn production in Jambi Province, prices at the rice and corn farmer levels, NPK fertilizer prices, and farm labor wages in Jambi Province. This study uses secondary data from the Central Statistics Agency and the Directorate General of Food Crops. Data collection was carried out using literature and documentation methods. Multiple regression analysis using ordinary least squares (OLS) was used to test how strong the influence of the independent variable (X) was on the dependent variable (Y). Still, data processing was operated with Eviews or SPSS software. Before testing using OLS, classical assumption tests such as multicollinearity tests, normality tests, autocorrelation tests, and heteroscedasticity tests were first carried out. The factors that influence the exchange rate of farmers in the food crop subsector in Jambi Province, namely prices at the rice farmer level, prices at the corn farmer level, rice production, and corn production, have a significant positive effect. The price of NPK fertilizer and farm laborers' wages significantly negatively affect the farmer's exchange rate. The price variables at the rice and corn farmer level and rice and corn production have a significant positive effect on the farmer's exchange rate in the food crop subsector in Jambi Province. Increasing selling prices and production can improve the Farmer's Exchange Rate in Jambi Province.